A vision of fire - Anderson, Gillian, 1968-; Rovin, Jeff (Anderson, Gillian, 1968- Earthend saga, 2014)
"Renowned child psychologist Caitlin O'Hara is a single mom trying to juggle her job, her son, and a lackluster dating life. Her world is suddenly upturned when Maanik, the daughter of India's ambassador to the United Nations, starts speaking in tongues and having violent visions. Caitlin is sure that her fits have something to do with the recent assassination attempt on her father--a shooting that has escalated nuclear tensions between India and Pakistan to dangerous levels--but when teenagers around the world start having similar outbursts, Caitlin begins to think that there's a more sinister force at work"--